Phospholipase D and Phosphatidic Acid-Mediated Generation of Superoxide in Arabidopsis - Sang, Yongming (American Society of Plant Physiologists, 2001)
Phospholipase D (PLD), which hydrolyzes phospholipids into free head groups and phosphatidic acid (PA), may regulate cellular processes through the production of lipid and lipid-derived messengers. We have genetically abrogated PLDα, the most prevalent isoform of PLD in plants, and the depletion of PLDα in Arabidopsis decreased the levels of PA and superoxide production in Arabidopsis leaf extracts. Addition of PA promoted the synthesis of superoxide in the PLDα-depleted plants, as measured by chemiluminescence and superoxide dismutase-inhibitable, NADPH-dependent reduction of cytochrome c and nitroblue tetrazolium. The PA-enhanced generation of superoxide was associated mainly with microsomal membranes. Among various lipids tested, PA was the most effective stimulator with the optimal concentrations between 100 and 200 μm. The PA-promoted production of superoxide was observed also in leaves directly infiltrated with PA. The added PA was more effective in stimulating superoxide generation in the PLDα-depleted leaves than in the PLDα-containing, wild-type leaves, suggesting that PA produced in the cell was more effective than added PA in promoting superoxide production. These data indicate that PLD plays a role in mediating superoxide production in plants through the generation of PA as a lipid messenger.